(untitled) (Global Journal of Medical Research, 2013)
The prevalence of Sal typhi in the various locations in Ekiti state over the years of 2009 -2011 was investigated. The highest number of the isolates from 50 samples was found at Ikere-Ekiti, Ikole-Ekiti and Ifaki Ekiti at a total number of 131 respectively, this was followed by Ado-Ekiti with an isolate number of 130. The lowest number of isolate was recorded at Ido Ekiti with 78 isolates in the year 2009 and this increased in both 2010 and 2011. The susceptibility patterns reported in 2009 in the different locations showed that resistance was indicated in streptomycin, chloramphenicol, cefepime, nalidixic acid tetracycline and trimethoprim-sulfamethoxazole. This same trend of resistance was repeated in 2010 and 2011. The notable change was a significant increase in the resistance to ampicillin from 20% to 100% in Ado Ekiti and from 39% to 100% at Ikole Ekiti and also Gentamycin from 18% at Ikere-Ekiti in 2009, to 86% and 84% in 2010 and 2011 respectively. The difference in demographic factors in the different locations could be a convincing factor in the prevalence of Sal typhi. With PFGE, a total of thirty-five 35 (79%) patterns in the locations were observed and thirty-six 36(72%) of each isolates had the 3 most common patterns. The isolates with these patterns were found to show high resistance to Streptomycin, Chloramphenicol, Cefepime, Ampicilin and nalidixic acid (SCCAN). All isolates that are resistant to the antibiotics mentioned earlier contain qnrB2, 35(70%) isolates contained blaCMY-2′; 39 (78%) isolates contained blaCMY-23′ the mechanism for extended-spectrum cephalosporin, Aminoglycosides and Quinolone resistance. The genes that code for this resistance have proven to be remarkably mobile and widely distributed within and between species.